Absurdity in the second Higri age promiscuity poetry (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Absurdity is a linguistic term that implies  multiple meanings such as confusion and belittling, and it is an act that does not reveal any meaning, so disregard comes above the law, and carries within it ridicule and rebellion against the fixed answers . At the same time, and promiscuity is the open literature that holds within  skepticism, atheism, arrogance, contempt and recklessness. It also implies  rebellion against the constant whether literature, art, life or religion. This term appeared in the Greek philosophy of the Epicurean philosophers and in modern philosophies where it was discussed by existentialists such as Heidegger, Kierkegaard, Sartre, Albert Camus  among others This research seeks to studying the absurdity of the free poets in the second century AH; As that era was actually distinguished from others by its economic and intellectual prosperity, and its poets were distinguished by deep culture and familiarity with incoming cultures and philosophies.